(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
In the article to descry function gustatory vocabulary in the work Literature. The to mark degree respect author and characters the dish and process preparation to display trade utilization author the gustatory vocabulary.